Bilateral gradual cortical blindness due to hemodynamic stroke: A case report - Adelheid Loraine Erensina Rumbiak, MD; Achmad Firdaus Sani, MD; Dedy Kurniawan, MD; Ida Ahadiyati, MD (Radiology Case Reports, 2023)
Cortical blindness refers to the loss of vision caused by a lesion affecting the geniculate calcarine visual pathway. Bilateral occipital lobe infarctions in the vascular territory of the posterior cerebral arteries are the most common cause of cortical blindness. However, bilateral cortical blindness gradual is rarely reported. Gradual bilateral blindness usually occurs in lesions other than stroke, such as tumors. We report a case of a patient with gradual cortical blindness caused by a nonocclusive stroke caused by hemodynamic compromise. A 54-year-old man diagnosed with bilateral cerebral ischemia after complaining of bilateral gradual vision loss and headache for 1 month. Initially, he only complained of blurred vision with >2/60 vision. However, his visual acuity worsened until he could only see hand movements and only light perception later on (with visual acuity of 1/∼). A computed tomography scan of the head revealed a bilateral occipital infarction, and cerebral angiography revealed multiple stenoses and near-total occlusion of the left vertebral artery ostium, underwent angioplasty and stenting. He has received dual antiplatelet and antihypertensive treatment. He got visual improvement with visual acuity 2/300 after 3 months of the treatment and procedure. Gradual cortical blindness caused by hemodynamic stroke is rare. The most common cause of posterior cerebral arteries infarction is embolism from the heart or vertebrobasilar circulation. With proper management and focusing on treating the etiology of these patients, vision improvements can be obtained in these patients.